Dhikrullah Vibration as Emotional Counseling Amongs the Aceh Community - Iskandar Ibrahim (Budapest International Research and Critics University, 2021)
Dhikrullah is an Islamic teaching to get calm has not been used in emotional counseling. The relationship between sound vibrations and emotions is still being studied in the acoustic room. M. J. Griffin has analyzed the benefits of vibration for humans. Neuroscience explains that emotional stability can help increase one's awareness. This paper discusses the role of dhikrullah vibration as emotional counseling among Acehnese people from a scientific approach. Qualitative data was sourced from 10 dhikrullah leaders in North Aceh and 3 dhikrullah leaders in Medan, North Sumatra. For quantitative data obtained through the Electro Encephalo Graph in order to get a sample of 10 subjects. The first finding, the vibration of dhikrullah. Second, dhikrullah as counseling and third, dhikrullah as emotional counseling among the Aceh Temun people from this study will contribute to four aspects. First, the development of Islamic mysticism. Second, increasing public awareness of dhikrullah as emotional therapy in the brain. Third, to explain dhikrullah as a legacy of Sufism scholars. Fourth, to resolve the incomplete mental problems in Aceh. The government can adopt the results of this study into public policy as social capital to strengthen the application of Islamic values in Aceh. The government can recommend a dhikrullah counseling approach to mental hospitals, prisons, nursing homes, trauma rehabilitation centers and drug rehabilitation centers.